Business research methods - Schindler, Pamela S. (New York : McGraw-Hill, 2022)
"A transformation is taking place in many of our classrooms. During the last decade, more and more of our students have transformed to visual-from verbal-learners. Visual learners need pictures, diagrams, and graphs to clarify and reinforce what the text relates. Integrated research process exhibits reveal a rich and complex process in a visual way. 31 fully integrated research process exhibits link concepts within stand alone chapters"--
Includes index.
Keywords: Industrial management -- Research